PENGEMBANGAN MEDIA ARISAN ANTIK PADA PEMBELAJARAN BILANGAN BULAT DI KELAS INKLUSI SD SWASTA AL-AZHAR BUKITTINGGI - Mulia, Ezi; Hanani, Silfia; Simbolon, Ali Mustopa Yakub; Yanti, Ira; Syafitri, Aisyah; Devi, Indra (Jurnal Dedikasi Pendidikan, 2024)
Making this innovative work aims to increase motivation and student learning outcomes in learning negative and positive integers by using Antique Arisan media (Manual and Electric Number Lines). This innovative work is the development of a number line media made using a board with an attractive appearance using green led lights on positive integers, red led lights on negative integers, each number is embossed for students with special needs, namely the blind and low vision. How to operate this media in two ways. (1) Use of this media by pressing the switch for each number to be addressed to complete simple number operations such as addition and subtraction of negative and positive integers. (2) Using a rail equipped with a toy that moves forward to show the addition of numbers, moves backwards for integer subtraction operations, this rail is installed under the number line which functions as a substitute for carrying out negative and positive integer operations using the number line, if the use of lights cannot be used because there is no power source. This use helps regular students and especially students with special needs in adding and subtracting negative and positive integers, so that students with special needs are served according to their needs and can solve problems encountered related to adding and subtracting integers, so that learning outcomes can increase.